2018
DOI: 10.1186/s12904-018-0377-2
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the needs of terminally-ill patients in Bosnia-Herzegovina: patients’ perceptions and expectations

Abstract: BackgroundMany terminally ill patients in Bosnia-Herzegovina (BiH) fail to receive needed medical attention and social support. In 2016 a primary healthcare centreer (PHCC) in Doboj (BiH) requested the methodological and technical support of a local partner (Fondacija fami) and the Geneva University Hospitals to address the needs of terminally ill patients living at home. In order to design acceptable, affordable and sustainable solutions, we involved patients and their families in exploring needs, barriers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Consistent with previous research in both developed and developing countries [ 28 , 42 – 45 , 70 , 71 ], both cancer and non-cancer patients in Bhutan have varied needs throughout their illness that affects their overall QOL—ranging from physical symptom control to psychological, emotional, cognitive and spiritual support, as well as the need for food and financial assistance. Patients also had information needs about diagnosis, treatment options and side effects along with the need for psychological and spiritual support [ 35 , 72 ].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Consistent with previous research in both developed and developing countries [ 28 , 42 – 45 , 70 , 71 ], both cancer and non-cancer patients in Bhutan have varied needs throughout their illness that affects their overall QOL—ranging from physical symptom control to psychological, emotional, cognitive and spiritual support, as well as the need for food and financial assistance. Patients also had information needs about diagnosis, treatment options and side effects along with the need for psychological and spiritual support [ 35 , 72 ].…”
Section: Discussionsupporting
confidence: 73%
“…The needs of patients with non-malignant conditions are now increasingly identified [39][40][41]. This research found that people diagnosed with advanced malignant and non-malignant illnesses in Bhutan have poor levels of functioning and varied levels of symptom severity indicating high support needs, consistent with advanced illnesses in other LMICs [33,[42][43][44][45]. There was no differences in symptom severity or level of functioning between cancer and non-cancer patients except for constipation (p value < 0.05).…”
Section: Discussionmentioning
confidence: 71%
“…The needs of patients with non-malignant conditions are now increasingly identi ed [39][40][41]. This research found that people diagnosed with advanced malignant and non-malignant illnesses in Bhutan have poor levels of functioning and varied levels of symptom severity indicating high support needs, consistent with advanced illnesses in other LMICs [33,[42][43][44][45]. There was no differences in symptom severity or level of functioning between cancer and non-cancer patients except for constipation (p value < 0.05).…”
Section: Discussionmentioning
confidence: 72%
“…The needs of patients with non-malignant conditions are now increasingly identi ed [39][40][41]. This research found that people diagnosed with advanced malignant and nonmalignant illnesses in Bhutan have poor levels of functioning and varied levels of symptom severity indicating high support needs, consistent with advanced illnesses in other LMICs [33,[42][43][44][45]. There was no differences in symptom severity or level of functioning between cancer and non-cancer patients except for constipation (p value < 0.05).…”
Section: Discussionmentioning
confidence: 72%